2019
DOI: 10.3390/pharmaceutics11120642
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Human Thrombus by Liposomes Modified with Anti-Fibrin Protein Binders

Abstract: Development of tools for direct thrombus imaging represents a key step for diagnosis and treatment of stroke. Nanoliposomal carriers of contrast agents and thrombolytics can be functionalized to target blood thrombi by small protein binders with selectivity for fibrin domains uniquely formed on insoluble fibrin. We employed a highly complex combinatorial library derived from scaffold of 46 amino acid albumin-binding domain (ABD) of streptococcal protein G, and ribosome display, to identify variants recognizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…In this study, we formulated D7H2-proteoliposomes in the Z-average size of 250 nm, dual-labelled using lyssamine-rhodamine, and Gd-PE for FLI and MRI, respectively. D7H2 protein was previously reported to bind to clots prepared from human whole blood [31]. Here, we also proved the specific binding to artificial clots prepared from the TISSEEL kit (Figure S3).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In this study, we formulated D7H2-proteoliposomes in the Z-average size of 250 nm, dual-labelled using lyssamine-rhodamine, and Gd-PE for FLI and MRI, respectively. D7H2 protein was previously reported to bind to clots prepared from human whole blood [31]. Here, we also proved the specific binding to artificial clots prepared from the TISSEEL kit (Figure S3).…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, dual-labelled D7H2-modified liposomes were employed for both clot targeting (whole blood clots), and also clot pre-labelling and consequent imaging using FLI and MRI (artificial fibrin clots). Modification of liposomes using D7H2 and its physical chemical characterization was described in detail previously [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to previously used three-helix bundle ABD-derived combinatorial library [30][31][32], here we demonstrate a new loop-randomized scaffold library designed on the structure of domain 10 of human contractile muscle protein myomesin-1. After the screening of randomized library designated as Myomedin library, the best 10E8 binders were identified, produced in prokaryotic expression system, and used as immunogens in experimental mice to stimulate the production of specific antibodies.…”
Section: Introductionmentioning
confidence: 90%
“…Herein, we were concerned with the albumin-binding domain (ABD) derived from the streptococcal protein G. ABD is a 46-residue peptides, which has a very high binding affinity with human, monkey and mouse albumins ( 20 ). Previous studies showed that ABD could efficiently direct the coupled substances to dLNs, and could increase their retention times and stabilities in vivo ( 21 ).…”
Section: Introductionmentioning
confidence: 99%